Health Belief Model (HBM) pada Pasien Tuberculosis (TB) - Shabrina Fitri Rahmadini; Tutut Chusniyah; Indah Yasminum Suhanti (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2021)
The main focus of this study was to find out how the health belief model (HBM) in tuberculosis patients, ie by knowing how to believe in seriousness, susceptibility, benefits, and barriers. This research is a qualitative research with generic qualitative research design. The subject of this study were 5 tuberculosis patients at Dinoyo Health Center. The result shows that TB sufferers have good confidence in the seriousness, susceptibility, benefits and barriers of TB disease. Patients get enough information about TB disease through health workers. Patients do not stop the treatment despite experiencing side effects of treatment. Patients feel getting more benefit by completing treatment. Patients get both social and economic support.